1997
DOI: 10.1021/bi961848w
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metalloprotease in Rat Brain Cleaves the Amyloid Precursor Protein of Alzheimer's Disease Generating Amyloidogenic Fragments

Abstract: The amyloid protein (A beta or beta A4) is the major constituent of amyloid plaques in the Alzheimer's disease brain. A beta is cleaved from the amyloid precursor protein (APP) by a mechanism which is poorly understood. Cell culture studies suggest that APP may be cleaved by secretases within the late Golgi compartment. Studies performed so far have mainly used exogenous APP and synthetic peptides as substrates. For this study, a Golgi and plasma membrane-enriched fraction was isolated from rat brain and incub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…The Golgi apparatus plays a critical role in the process of secretion (8,24,32) and numerous resident proteins such as galactosyltransferase and metalloproteases are Zn dependent (30,33). We found that changes in ZnT4 abundance modulated the activity of galactosyltransferase.…”
Section: Discussionmentioning
confidence: 76%
“…The Golgi apparatus plays a critical role in the process of secretion (8,24,32) and numerous resident proteins such as galactosyltransferase and metalloproteases are Zn dependent (30,33). We found that changes in ZnT4 abundance modulated the activity of galactosyltransferase.…”
Section: Discussionmentioning
confidence: 76%
“…Membranes were blocked in 0.5% hydrolysed casein in phosphate‐buffered saline (PBS), pH 7.4, for 1 h. The blocked membranes were then incubated with 12.5 µg/mL biotinylated lectin in Tris‐buffered saline–Tween 20 (TBST) for 1 h at room temperature (22 °C). After washing the membranes with TBST, glycoproteins were visualized using (1 : 1000 dilution) NeutrAvidin‐conjugated to alkaline phosphatase and developed with a mixture of Fast Red/naphthol AS‐MX substrate (Mok et al . 1997).…”
Section: Methodsmentioning
confidence: 99%
“…A number of proteases can cleave APP in vitro including the cathepsins D and G [32], calpain [33], thrombin [34], metalloprotease (EC 3.4.24.15) [35], gelatinase A [36,37], calcium‐activated serine protease [38], and Factors XIa [39] and Xa [40]. Our studies have identified a novel metalloprotease in a Golgi‐enriched fraction from rat brain which cleaves APP in vitro [41]. This Zn 2+ ‐dependent enzyme generates several potentially amyloidogenic fragments ranging in molecular mass from 14 kDa to 80 kDa.…”
mentioning
confidence: 99%